Job Readiness elements for hospitality graduates: a pilot study - Anies Faziehan Zakaria,; Noorzella Bokhari,; Azman Hasan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Job readiness questionnaire was developed to measure the level and important element for hospitality graduate. A pilot study was conducted in order to determine the reliability and validity of the questionnaire. There are six constructs were identified such as communication, problem solving, ICT, organization and leadership teamwork, workplace attitude, self-management, and technical skills for this questionnaire. A total of 30 lecturers from Kolej Vokasional Setapak were selected to participated in this survey. Rasch Measurement Model (i.e., PTMEA CORR, item fit, item polarity) was used to analyse the responses using Winsteps. This study found that PTMEA CORR has a positive value, in which items are able to differentiate the capabilities of the respondents. Besides, the results of infit and outfit mean square are ranged between 0.60 and 1.4. The quality of items is high because the reliability value is also high. In addition, the separation of item and person is at the acceptable range. However, statistical data shows that 8 out of 122 items have been dropped.